Language in public spaces : language choice in two IsiXhosa speaking communities (Langa and Khayelitsha) - Dantile, Andiswa Mesatywa (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.